Are children less reliable at making visual identifications than adults? A review - Havard, Catriona (2014)
The current paper reviews research that has investigated developmental differences in lineup identification. A wealth of studies have shown that children can be as accurate as adults when making a correct identification from a target present lineup (TP), however children are more inclined to choose and thereby make a false identification from a target absent (TA) lineup, as compared to adults. The literature reviewed, suggests that the disparity between children’s and adult’s performances on TA lineups is due to children being unable to resist the social demands to choose someone from a lineup and/or the need to give a positive response. Employing a silhouette within a lineup, that can be chosen if the target is not recognised, appears to be the most successful technique for reducing false identifications made by child witnesses. Including a silhouette as a part of a lineup, along with the lineup administrator being attired in casual clothing, rather than a uniform, are two simple measures that could make child witness identification evidence more reliable